2012
DOI: 10.1590/s1516-44462012000500008
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol, a Cannabis sativa constituent, as an anxiolytic drug

Abstract: Future clinical trials involving patients with different anxiety disorders are warranted, especially of panic disorder, obsessive-compulsive disorder, social anxiety disorder, and post-traumatic stress disorders. The adequate therapeutic window of CBD and the precise mechanisms involved in its anxiolytic action remain to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 31 publications
0
39
0
12
Order By: Relevance
“…Current research is looking at such anxiety disorders as social anxiety disorder, posttraumatic stress disorders, panic disorder, and obsessive-compulsive disorder (69, 70). …”
Section: Prevalencementioning
confidence: 99%
“…Current research is looking at such anxiety disorders as social anxiety disorder, posttraumatic stress disorders, panic disorder, and obsessive-compulsive disorder (69, 70). …”
Section: Prevalencementioning
confidence: 99%
“…Cannabidiol (CBD) is one of the most abundant cannabinoids in the marijuana plant (Mechoulam & Shvo, 1963; Mechoulam & Hanuš, 2002; Schier et al, 2012). It is a promising candidate for clinical utilization, due to low affinity binding to CB1 and CB2 cannabinoid receptors and no cognitive and psychoactive activity (Zuardi, 2008; Deiana, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In sum, existing research seems to undermine Schier's et al (2012) suggestion regarding the lack of a relationship between CBD and cognition. Rather, it seems that both cognitive and affective consequences of CBD administration may be mediated by the ACC.…”
Section: Resultsmentioning
confidence: 65%
“…The therapeutic value of CBD in clinical contexts is currently being explored (Zuardi et al, 2006, 2009; Hallak et al, 2009). Moreover, in a recent review Schier et al (2012) suggested that CBD neither produces psychoactive effects, nor has an impact on cognition. In the light of up-to-date research, this claim may be considered unwarranted, since CBD has been shown to differ with THC in terms of activation of brain regions during tasks involving response inhibition (Borgwardt et al, 2008), emotional processing (Fusar-Poli et al, 2009) and verbal memory (Bhattacharyya et al, 2010).…”
Section: Introductionmentioning
confidence: 99%